Trading Volume and Fama-French Three Factor Model on Excess Return. Empirical Evidence from Nairobi Security Exchange - Opuodho Gordon Ochere; Nasieku M. Tabitha; Olweny Tobias O (European Scientific Journal, ESJ, 2018)
The main objective of this paper is to examine the effect of Trading Volume on excess return using the Fama-French three factor model of listed companies in Kenya. The research study employed a Quantitative research design to analyses the effect of Trading Volume on excess returns in Nairobi Security Exchange (NSE) during the period 2006 to 2015. Secondary data was used for this study. The study utilized descriptive statistics, correlation, unit root test, Heteroscedasticity, and Autocorrelation test as diagnostic tests. The regression results revealed that Market premium and Value premium (HML) and Trading Volume have a high explanatory power while the size premium (SMB) has a low explanatory power.